2012
DOI: 10.1371/journal.pone.0047934
|View full text |Cite
|
Sign up to set email alerts
|

Dopaminergic Modulation of Effort-Related Choice Behavior as Assessed by a Progressive Ratio Chow Feeding Choice Task: Pharmacological Studies and the Role of Individual Differences

Abstract: Mesolimbic dopamine (DA) is involved in behavioral activation and effort-related processes. Rats with impaired DA transmission reallocate their instrumental behavior away from food-reinforced tasks with high response requirements, and instead select less effortful food-seeking behaviors. In the present study, the effects of several drug treatments were assessed using a progressive ratio (PROG)/chow feeding concurrent choice task. With this task, rats can lever press on a PROG schedule reinforced by a preferred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
184
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 175 publications
(214 citation statements)
references
References 67 publications
26
184
1
3
Order By: Relevance
“…Experiment 1 demonstrated that the DA D 2 receptor antagonist haloperidol, at both doses tested, decreased the breakpoint, number of lever presses, number of reinforcers obtained, and increased intake of freely available laboratory chow. Our results are in line with previous work that has carefully described the role of DA mechanisms on this lever pressing and chow feeding task [52,53,58]. DA antagonism and striatal depletions by 6-OHDA or tetrabenazine have been shown to decrease measures of lever pressing while resulting in compensatory increases in chow intake.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Experiment 1 demonstrated that the DA D 2 receptor antagonist haloperidol, at both doses tested, decreased the breakpoint, number of lever presses, number of reinforcers obtained, and increased intake of freely available laboratory chow. Our results are in line with previous work that has carefully described the role of DA mechanisms on this lever pressing and chow feeding task [52,53,58]. DA antagonism and striatal depletions by 6-OHDA or tetrabenazine have been shown to decrease measures of lever pressing while resulting in compensatory increases in chow intake.…”
Section: Discussionsupporting
confidence: 92%
“…Saline served as the vehicle control for all naloxone experiments. Doses of haloperidol and naloxone were selected from previously published data [52][53][54][55]. All injections were delivered intraperitoneally (IP).…”
Section: Pharmacological Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regions deemed inessential in physical effort (eg, the prefrontal cortex; Walton et al, 2003b) have been shown to have a prominent role in human cognitive effort Schmidt et al, 2012). Furthermore, these human studies have emphasized how individual differences in brain function influence individual differences in effort expenditure (Treadway et al, 2012b), an examination all but absent from animal effort literature (but see Randall et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, there can be barriers for making such a switch: most importantly, to introduce the use of high incentive rewards would increase the behavioural baseline response. The incentive value of rewards as demonstrated behaviourally is known to be significantly affected by quite minor changes to experimental procedure such as a change in the reinforcer in use (Randall et al 2012). Behavioural analyses of reinforcement-value measure responding on schedules requiring animals to make progressively more and more responses (such as pressing a lever within a Skinner box) to secure the same level of food reward.…”
Section: Rules and Recommendations: The Need For Flexibilitymentioning
confidence: 99%